IMPLEMENTASI KURIKULUM 2013 REVISI DALAM PEMBELAJARAN PENDIDIKAN AGAMA KATOLIK : (Suatu Tinjauan Kritis Terhadap Kompetensi dan Problematika Guru PAK di Sekolah-Sekolah Se-Kecamatan Tanimbar Selatan) - Reresi, Marsianus; Seralarat, Kornelis (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2018)
The 2013/revision Curriculum is a furture development of earlier curricula, in which the implementation of the teacher’s competence in matters of religious instruction is imperative. Focus of the qualitative research is how are the competency and problematics of teacher’s implementing the 2013/revision curriculum of Catholic Religious instruction at the schools in the South Tanimbar District? The result of this investigation is being studied analticall in the context of Catholic Religion teacher’s competency and problematics wich occur when the 2013/revision curriculum of Catholic religious instruction is being implemented.